The impact of airway management guided by Protection Motivation Theory on the prevention and prognosis of post-stroke pneumonia - Liu, Qiaoyun; Wang, Liuqing; Xia, Pan; Li, Lanjuan; Zhao, Chen; Liu, Siqi; Xu, Shanshan (Frontiers in Neurology, 2025)
BackgroundStroke remains a leading cause of morbidity and mortality worldwide, with post-stroke pneumonia significantly impacting patient outcomes. Despite progress in stroke management, there was a lack of emphasis on targeted preventive measures for pneumonia. This study evaluates the impact of airway management guided by Protection Motivation Theory (PMT) on preventing post-stroke pneumonia.MethodsA retrospective study was conducted with 100 stroke patients admitted to the general neurology ward between January and December 2023. Patients were divided into two groups based on chronological admission order: 50 received standard airway management (January–June 2023), and 50 received PMT-guided intervention (July–December 2023). The PMT group engaged in structured educational sessions (30 min daily for 7 days) and actionable coping strategies to enhance adherence to airway management. Outcomes assessed included incidence of post-stroke pneumonia (diagnosed by chest CT within 7 days post-admission), respiratory function, length of hospital stay, and cognitive and psychological measures.ResultsThe PMT group showed a lower incidence of pneumonia (16% vs. 34%, p = 0.038) and reduced hospital stay (13.47 ± 3.86 days vs. 15.72 ± 4.36 days, p = 0.007). The absolute risk reduction was 18% with a number needed to treat (NNT) of 5.6. Improvements were noted in respiratory function, with higher forced vital capacity (2.46 ± 0.68 L vs. 2.15 ± 0.56 L, p = 0.013). Cognitive function, as measured by the Montreal Cognitive Assessment, was enhanced (23.58 ± 4.06 vs. 21.35 ± 3.84, p = 0.006), with both groups remaining below the normal threshold of 26 points. Depression levels were reduced (PHQ-9: 12.05 ± 3.12 vs. 13.46 ± 3.56, p = 0.038).ConclusionPMT-guided airway management significantly enhances post-stroke outcomes through improved respiratory function, reduced pneumonia incidence, and better cognitive and psychological wellbeing. Future prospective studies with larger sample sizes are warranted to validate these findings.